Helmholtz decomposition theorem and Blumenthal's extension by regularization - Petrascheck, D.; Folk, R. (Condensed Matter Physics, 2017)
Helmholtz decomposition theorem for vector fields is usually presented with too strong restrictions on the
fields and only for time independent fields. Blumenthal showed in 1905 that decomposition is possible for
any asymptotically weakly decreasing vector field. He used a regularization method in his proof which can be
extended to prove the theorem even for vector fields asymptotically increasing sublinearly. Blumenthal’s result
is then applied to the time-dependent fields of the dipole radiation and an artificial sublinearly increasing field. Теорема про розвинення Гельмгольца для векторного поля зазвичай представляється з сильними обмеженнями на поле i лише для незалежних вiд часу полiв. У 1905 р. Блюменталь показав, що розвинення
є можливим для любого асимптотично слабоспадного векторного поля. Вiн використав у доведеннi регуляризацiйний метод, який можна було розширити для доведення теореми для векторних полiв, що є
асимптотично сублiнiйно висхiдними. Результат Блюменталя застосовано до часовозалежних полiв дипольного випромiнення i штучного сублiнiйно висхiдного поля.